Improvement of composite wood properties made from wood waste chips - Wong, Yiik Ching. (Universiti Malaysia Sarawak, UNIMAS, 2009)
Producing composite wood such as particleboard is a great way to recycle wood waste produced from the industrial activities. Particleboard is widely used due to its low cost and controllable specification. Therefore, improving the properties of the particleboard is an important task in order to extend the potential of particleboard for greater performance and more diversity of applications. The aim of this study is t o improve the mechanical and physical properties of particleboard by using surface coating. The surface coatings chosen for the project are polyurethane wood varnish, gloss paint, lacquer paint, and wood veneer. Surface coatings were used on the particlebo ard to achieve improvements on modulus of elasticity, modulus of rupture, moisture absorption and thickness swelling. Test results obtained were analyzed to determine the effectiveness of each surface coating to improve the particleboards. Result obtained from the tests showed that wood veneer could effectively improve the mechanical properties of the particleboard while polyurethane wood varnish was excellent in enhancing the physical properties of particleboard. Nevertheless, each surface coating has diff erent characteristics and properties which can improve the particleboard in its unique way. The data on the improvements achieved by each surface coating could become useful reference for manufacturers and users to select suitable coatings for particleboar ds with specific application.